2011
DOI: 10.1007/s10869-011-9214-9
|View full text |Cite
|
Sign up to set email alerts
|

Being Successful in a Creative Profession: The Role of Innovative Cognitive Style, Self-Regulation, and Self-Efficacy

Abstract: PurposeThe purpose of this study was to test a model that proposes that innovative cognitive style and self-regulation (setting priorities, planning work activities, and monitoring time and task progress) are related to the self-reported success of architects. We investigated two aspects of the success: as designers and as business people. To this end, we examined the mediating role of self-efficacy in these relationships.Data/Methodology/ApproachWe collected data using a web-based survey among 276 architects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(38 citation statements)
references
References 51 publications
1
36
0
1
Order By: Relevance
“…A recent empirical study on Dutch architects showed that innovative cognitive style indirectly relates to an architect's success in creative design through strengthening creative self-efficacy, an important predicator of individual creativity (Beeftink et al, 2012). On the other hand, proactive personality also plays an important role in determining an individual's creative potential.…”
Section: Disscussionmentioning
confidence: 99%
“…A recent empirical study on Dutch architects showed that innovative cognitive style indirectly relates to an architect's success in creative design through strengthening creative self-efficacy, an important predicator of individual creativity (Beeftink et al, 2012). On the other hand, proactive personality also plays an important role in determining an individual's creative potential.…”
Section: Disscussionmentioning
confidence: 99%
“…Psychological constructs such as some aspects of personality (Barrick & Mount, 1991, Tett, Jackson, & Rothstein, 1991; intelligence (Bertua, Anderson, & Salgado, 2005); Resilience (Avey, Reichard, Luthans, & Mhatre, 2011); and self-regulation (Beeftink, Van Eerde, Rutte, & Bertrand, 2012) have been shown to relate to job performance for an ever increasing number of fields. The inclusion of these factors in the present study is based on the teacher selection model recently proposed in which personality, Resilience and self-regulation are regarded as key indicators for selection (Bowles, Hattie, Dinham, Scull, & Clinton, 2014).…”
Section: Characteristics Of Effective Teachersmentioning
confidence: 99%
“…They involve effectively seeking and using feedback to adjust and improve, managing time and seeking help when needed. Self-regulation is related to successful job performance in a range of professions (Ashford & Tsui, 1991;Beeftink et al, 2012;Lord et al, 2010) and a recent study found mathematics teachers classified as having high levels of self-regulation were given more favourable rating by students, and the students of such teachers reported feeling more component and autonomous in class (Klusmann et al, 2008). It is likely that teachers with self-regulatory skills manage their workload better and seek feedback on their teaching from students and colleagues, thus working to improve their teaching.…”
Section: Characteristics Of Effective Teachersmentioning
confidence: 99%
“…Creative self-efficacy also serves as a significant variable in predicting success in creative professionals (Beeftink et al 2012), professionals in non-creative industries (Chong and Ma 2010;Tierney and Farmer 2002), and undergraduate college students (Hung et al 2008). Beeftink et al (2012) examined 276 successful architects in the Netherland and reported that self-efficacy played a key role in mediating the relation between innovative cognitive style and success in the creative profession regardless the size of the architectural business organizations.…”
Section: Pro-c Creativitymentioning
confidence: 99%
“…Beeftink et al (2012) examined 276 successful architects in the Netherland and reported that self-efficacy played a key role in mediating the relation between innovative cognitive style and success in the creative profession regardless the size of the architectural business organizations. Creative self-efficacy plays a pivotal role in predicting Pro-c creativity in architects.…”
Section: Pro-c Creativitymentioning
confidence: 99%